DETC induces Leishmania parasite killing in human in vitro and murine in vivo models: a promising therapeutic alternative in Leishmaniasis. - Ricardo Khouri (Public Library of Science (PLoS), 2010)
Background Chemotherapy remains the primary tool for treatment and control of human leishmaniasis. However, currently available drugs present serious problems regarding side-effects, variable efficacy, and cost. Affordable and less toxic drugs are urgently needed for leishmaniasis. Methodology/principal findings We demonstrate, by microscopy and viability assays, that superoxide dismutase inhibitor diethyldithiocarbamate (DETC) dose-dependently induces parasite killing (p<0.001) and is able to "sterilize" Leishmania amazonensis infection at 2 mM in human macrophages in vitro. We also show that DETC-induced superoxide production (p<0.001) and parasite destruction (p<0.05) were reverted by the addition of the antioxidant N-acetylcysteine, indicating that DETC-induced killing occurs through oxidative damage. Furthermore, ultrastructural analysis by electron microscopy demonstrates a rapid and highly selective destruction of amastigotes in the phagosome upon DETC treatment, without any apparent damage to the host cell, including its mitochondria. In addition, DETC significantly induced parasite killing in Leishmania promastigotes in axenic culture. In murine macrophages infected with Leishmania braziliensis, DETC significantly induced in vitro superoxide production (p = 0.0049) and parasite killing (p = 0.0043). In vivo treatment with DETC in BALB/C mice infected with Leishmania braziliensis caused a significant decrease in lesion size (p<0.0001), paralleled by a 100-fold decrease (p = 0.0087) in parasite burden. Conclusions/significance Due to its strong leishmanicidal effect in human macrophages in vitro, its in vivo effectiveness in a murine model, and its previously demonstrated in vivo safety profile in HIV treatment, DETC treatment might be considered as a valuable therapeutic option in human leishmaniasis, including HIV/Leishmania co-infection.